Analisis Pengaruh Indeks Pembangunan Manusia Terhadap Jumlah Penduduk Miskin Pada Provinsi Banten - Dwi Pitaloka, Dyah Ayu; Awalluna, Kharisma Zahro; Desmawan, Deris (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study is an analysis of data from BPS Banten sources and aims to identify the impact of the Human Development Index on the poverty headcount in Banten over the period 2012-2021. Determined by applying a simple linear regression method using the variables. A supporting application, by SPSS or Statistical Product and Service Solutions.